TRANSPORT MODEL FRAMEWORK FOR ZILINA - Gogola, Marian (Doprava a spoje, 2007)
The traffic problems are becoming the common part of our daily living. It's clear that we need to face to the problems and find out the solution which works. While abroad it is common that town have own transport model, the situation in Zilina certify the contrast. The aim of this contribution is describe transport model framework proposed for Zilina town so called Zilina Transport Model (ZTM). The model development preceded a couple year work where the model techniques were investigated. The main goal is develop such kind of model which will be universal and objective for transport and traffic problem solution.